2012
DOI: 10.1111/cns.12044
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Protects HT22 Neurons from H2O2‐induced Apoptosis by Inhibiting the MAPK Signaling Pathway

Abstract: Our results provide the first evidence that edaravone can protect H2O2-induced cell injury in HT22 neurons via its antioxidant action. These findings suggest that edaravone may be useful in the treatment of neurodegenerative disorders in which oxidative stress has been principally implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 35 publications
8
70
0
Order By: Relevance
“…UA has been demonstrated to trigger the upregulation of ROS in several cell types. ROS are able to regulate or induce multiple cellular processes, including epithelial-mesenchymal transition (19), growth (20), cell differentiation (21) and apoptosis (7)(8)(9)13). The present study indicated that UA induced apoptosis in renal tubular cells by inducing ROS, which may cause cell loss and tubular dysfunction during the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UA has been demonstrated to trigger the upregulation of ROS in several cell types. ROS are able to regulate or induce multiple cellular processes, including epithelial-mesenchymal transition (19), growth (20), cell differentiation (21) and apoptosis (7)(8)(9)13). The present study indicated that UA induced apoptosis in renal tubular cells by inducing ROS, which may cause cell loss and tubular dysfunction during the progression of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that mitogen-activated protein kinase (MAPK) pathways are activated by upregulation of intracellular ROS (12)(13)(14). P38 and ERK1/2 are important members of the MAPK family, which regulates cell growth and apoptosis (15)(16)(17).…”
Section: P38 and Erk1/2 Signaling Are Involved In Ua-induced Apoptosismentioning
confidence: 99%
“…17,18) To measure the cytosolic Ca 2+ concentration, the cells were incubated with 20 µM Fluo-4/AM and 1 µM pluronic F-127 for 20 min at 37°C in the dark. Fluorescence images were obtained using confocal laser-scanning microscopy, with 488 nm excitation wavelength and 510 nm detection wavelength.…”
Section: +mentioning
confidence: 99%
“…H 2 O 2 generation is required to mediate the complete sequence of events occurring in oxidative stress-induced neuronal cell death. 24) In previous studies, researchers employed H 2 O 2 overload as a neurotoxic challenge paradigm to evaluate aspects of neuroprotection in murine hippocampal HT22 cell. 25,26) The neuroprotective effect of C. (Fig.…”
Section: Resultsmentioning
confidence: 99%